2011
DOI: 10.1007/s10236-011-0415-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of the tidal representation in Singapore Regional Waters in a data assimilation environment

Abstract: The Singapore Regional Waters (SRW) is one of the more complex tidal regions in the world. This complexity is caused by various factors including the interaction of the Indian and Pacific oceans with their mainly semi-diurnal and diurnal tide, respectively, complicated coastline geometry, small islands and sharply varying bottom topography. Tidal data analysis is hampered by the lack of reliable coastal stations with long-term water level records while numerical tidal modelling studies suffer from lack of accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…First to investigate the semi-diurnal to diurnal co-tide phases interaction at the Singapore Strait, stronger impact to Singapore Strait's tidal condition than Andaman Sea. This is agreed by Kurniawan et al [22], which showed Java Sea stronger influence toward the tidal condition at Singapore Strait when compared to Andaman Sea using the tidal amplitude component study. …”
Section: Hydrodynamic Simulation: Model Validationsupporting
confidence: 88%
See 2 more Smart Citations
“…First to investigate the semi-diurnal to diurnal co-tide phases interaction at the Singapore Strait, stronger impact to Singapore Strait's tidal condition than Andaman Sea. This is agreed by Kurniawan et al [22], which showed Java Sea stronger influence toward the tidal condition at Singapore Strait when compared to Andaman Sea using the tidal amplitude component study. …”
Section: Hydrodynamic Simulation: Model Validationsupporting
confidence: 88%
“…However, the improvement in accuracy was usually restricted to only small simulated area (showed in [25,32]) or was not obvious in tidal current and water level simulations (showed in [19]). In comparison, by refining the local mesh resolution according to the local geometry can effectively improve the water levels and tidal currents simulation as proven in various studies (refer to studies by [9,21]), which it is also suggested to be a crucial element in the sensitivity analysis of SCW tidal simulations conducted by Kurniawan et al [22] and Sun et al [27].…”
Section: Introduction and Motivation Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a multi-dimensional hydrodynamic and transport simulation program which calculates non-steady flow and transport phenomena that result from tidal and meteorological forcing on a rectilinear or a curvilinear grid. Recently a similar study has been performed in Singapore Regional Waters (SRW) and detailed sensitivity analysis done to enhance the accuracy of tidal predictions using OpenDA in combination with long track satellite altimeter data [10]. It has clearly been indicated in this study that sub regions of SRW are very sensitive to forcing boundaries, depth and bottom friction and it is understood that uncertainties in physical parameters could be the source of error in such kind of numerical modelling studies.…”
mentioning
confidence: 84%
“…2). Curvilinear boundary fitted grid allows to overcome the uncertainties of model results compared to rectilinear grids [10]. In this study varying grid resolution was considered with decreasing element sizes (i.e.…”
mentioning
confidence: 99%